Double jeopardy [large type] - Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2021)
Stone Barrington is in New York when he receives news that demands immediate action. An old family matter has resurfaced, and Stone must decamp to the craggy shores of Maine to address the issue head-on. There, Stone finds that a dual-pronged threat is hiding in plain sight among the stately houses and exclusive coastal clubs, and the incursion isn't easily rebuffed. These enemies have friends in high places, funds to spare, and a score to settle with Stone--and only the cleverest plot will draw them out into the open. From luxuriously renovated homes to the choppy ocean waters, the pursuit can only lead to an explosive end.